Wetlands in the Environmental Assessment of the Proposed Chinchero Airport - Soria Dall’Orso, Carlos Antonio Martin (2020)
The article reviews an environmental assessment of a proposed airport in an area of high Andean wetlands with high natural, cultural and socioeconomic value. Besides a deficient base line, this paper proposes that a poor environmental certification and enforcement process allowed that the characterization of the environmental impacts of the proposed airport did not consider that the Chinchero high Andean wetlands are to be affected. The author reviews the applicable legal framework and concludes identifying actions that the authorities of the environmental management system must take to correct the insufficiencies and to be able to accurately assess the environmental impact of the proposed airport over the high Andean wetlands.